2021
DOI: 10.3390/ijms22115664
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Stent with mTOR Inhibitor-Eluting Reduces Progression of Ureteral Stricture

Abstract: In this study, we investigated the effect of mTOR inhibitor (mTORi) drug-eluting biodegradable stent (DE stent), a putative restenosis-inhibiting device for coronary artery, on thermal-injury-related ureteral stricture in rabbits. In vitro evaluation confirmed the dose-dependent effect of mTORi, i.e., rapamycin, on fibrotic markers in ureteral component cell lines. Upper ureteral fibrosis was induced by ureteral thermal injury in open surgery, which was followed by insertion of biodegradable stents, with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Ureteral strictures are generally reported to have several etiologies such as stones, surgical injuries, malignancy, and trauma ( 26 ). And we have found that stones, injuries and even sutures left over from surgery can lead to ureteral strictures.…”
Section: Discussionmentioning
confidence: 99%
“…Ureteral strictures are generally reported to have several etiologies such as stones, surgical injuries, malignancy, and trauma ( 26 ). And we have found that stones, injuries and even sutures left over from surgery can lead to ureteral strictures.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported investigations on ureteral stents with rapamycin inhibitor elution, paclitaxel-coated stents, bone 6588 marrow mesenchymal stem cells, and biodegradable stents in the prevention and treatment of ureteral stricture. [23][24][25][26] However, these treatments are only in the research stage and have not yet been applied in the clinic, and the efficacy of these drugs in the ureter deserves further study. Therefore, based on these previous studies, we tried to find a new one that could better combine the drug with the ureteral stent and simultaneously deliver the drug to the ureter accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, Ho et al investigated the impact of a drug-eluting biodegradable stent (DE stent) loaded with an mTOR inhibitor (mTORi) on ureteral stricture associated with thermal injury in rabbits ( Ho et al, 2021 ). The DE stent is a recognized device for inhibiting coronary artery restenosis.…”
Section: Future Clinical Applications Of Busmentioning
confidence: 99%